2018
DOI: 10.1002/jgm.3010
|View full text |Cite
|
Sign up to set email alerts
|

Low penetrance genetic polymorphisms as potential biomarkers for colorectal cancer predisposition

Abstract: Colorectal cancer is a leading form of cancer in both males and females. Early detection of individuals at risk of colorectal cancer allows proper treatment and management of the disease to be implemented, which can potentially reduce the burden of colorectal cancer incidence, morbidity and mortality. In recent years, the role of genetic susceptibility factors in mediating predisposition to colorectal cancer has become more and more apparent. Identification of high-frequency, low-penetrance genetic polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 164 publications
0
21
0
Order By: Relevance
“…For instance, while He et al 15 demonstrated that the variant allele of MIR499A rs3746444 polymorphism was significantly associated with an increased susceptibility to breast cancer, Morales et al 16 did not find any significant association. One of the major reasons for the inconsistency of study results in genetic association studies is the limited sample size and thus, low statistical power of the individual studies 17,18 . Therefore, in this work, we aimed to pool the study findings via a meta-analysis in order to derive a more precise estimate of the association between MIR499A rs3746444 polymorphism and breast cancer susceptibility.…”
mentioning
confidence: 99%
“…For instance, while He et al 15 demonstrated that the variant allele of MIR499A rs3746444 polymorphism was significantly associated with an increased susceptibility to breast cancer, Morales et al 16 did not find any significant association. One of the major reasons for the inconsistency of study results in genetic association studies is the limited sample size and thus, low statistical power of the individual studies 17,18 . Therefore, in this work, we aimed to pool the study findings via a meta-analysis in order to derive a more precise estimate of the association between MIR499A rs3746444 polymorphism and breast cancer susceptibility.…”
mentioning
confidence: 99%
“…Given the important role of ERα in BC, its level and structure need to be tightly regulated to ensure an optimal functionality. The level and structure of a protein are known to be influenced by, among others, genetic polymorphisms 59 . For this reason, many genetic association studies have investigated the relationship between ESR1 polymorphisms and BC susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study by Pietrzyk et al (2017) carried out in Poland with medical faculty students reported that the students had sufficient knowledge about the prevention of CRC. Furthermore, in a study carried out in Malaysia with the general population, it was stated that the majority of the participants had a good level of awareness on the issue (Mohd Suan, Mohammed, & Abu Hassan, 2015;Tan, 2018). It is hypothesised that students with awareness towards approaches for reducing the risk of CRC might develop such healthy lifestyles.…”
Section: Discussionmentioning
confidence: 99%